Preparation of Information Marketing Content on Instagram of the Amir Machmud Library, Ministry of Home Affairs of the Republic of Indonesia - Fadhillah, Arvyn (Nexus: Journal of Cross-Disciplinary Insights, 2025)
A special library is an institution that focuses on a collection of reading materials and specific information resources that support the specific needs and interests of a group or field of knowledge. The Amir Machmud Library is one of the libraries affiliated with the Indonesian Ministry of Home Affairs (Kemendagri). The Amir Machmud Library has utilized Instagram as a platform to promote various activities they do. The use of Instagram in information promotion institutions has grown along with the growth of Instagram users lately. Departing from this, this study aims to find out how to compile information marketing content on the Instagram of the Amir Machmud Library, Ministry of Home Affairs of the Republic of Indonesia. This study uses a qualitative research method with an Action Research approach. The results show that a content strategy that is structured and based on an analysis of real needs can increase the effectiveness of social media as an information marketing channel. The Amir Machmud Library, through its Instagram account, has transformed into an active actor in building a more open, participatory, and inclusive digital literacy culture and public education. In the future, existing challenges can be overcome with a collaborative approach, strengthening human resource capacity, and integrating social media as an important part of institutional communication strategies.